PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN INFOGRAFIS UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS X PS 1 SMK NEGERI 7 MAKASSAR - Nurfitrah Sasrianita Nurfitrah Sasrianita; Edi Suhardi Rahman (Jurusan Pendidikan Teknik Elektro, 2024)
This study aims to describe the improvement in student learning outcomes after participating in the learning process using the discovery learning model assisted by infographics. This classroom action research was conducted in two cycles with stages of planning, action, observation, and reflection. The research subjects were 37 students of class X PS 1 SMKN 7 Makassar, carried out in the even semester of the 2023/2024 academic year. Data collection techniques used written tests and documentation, with research instruments in the form of pretest and posttest sheets. Learning outcomes were analyzed using descriptive statistics. The research results showed a significant improvement in learning outcomes after the application of the discovery learning model assisted by infographics. The average class score increased from 39.59 in the pre-cycle to 70.81 in cycle I and 80.13 in cycle II. The completion percentage also increased from 40% in the pre-cycle to 71% in cycle I and 80% in cycle II. The implementation of discovery learning assisted by infographics was effective in improving student learning outcomes, making the learning process more conducive and meaningful.